Application of non-parametric approaches to identify trend in streamflow during 19762007 (Naula watershed) - Malik A.; Kumar A.; Najah Ahmed A.; Ming Fai C.; Abdulmohsin Afan H.; Sefelnasr A.; Sherif M.; El-Shafie A. (Elsevier B.V., 2023)
Catchments; Information management; Runoff; Stream flow; Time series; Water management; Watersheds; Climate change scenarios; Hydrological data; Nonparametric approaches; Positive/negative; River catchment; Sustainable planning; Temporal trends; Water resources management; Climate change